If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x=3)-1=3(x+6)
We move all terms to the left:
5(x-(3)-1)=0
We add all the numbers together, and all the variables
5(x-4)=0
We multiply parentheses
5x-20=0
We move all terms containing x to the left, all other terms to the right
5x=20
x=20/5
x=4
| (4x–7)(3x+5)=0 | | 3-6a=9-61 | | (D5+8D^3+16D)y=0 | | a+4=-a-4 | | -13p−3p=16 | | 2.5x-4=-9 | | 190.00+x(0.25)=337.50 | | (D^3-8D^2+16D)y=0 | | 890=5(x+17) | | 12•d=84 | | 12b+-15b=18 | | -2p+(-7p)-(5)=59 | | (12x-28)=(5x+1) | | 63+12m=15m | | 4x+1+8x-51=180 | | (5x+1)=(12x-28) | | 30-x=12.5 | | y–33+2y–23+50+31+2y=360 | | x=127/10 | | 4z+16=5z | | 2p+2p-46+32+30+52+44=360 | | 7x-3+x+11=180 | | 3+2p=5 | | 5x=8x+2 | | x+13÷100=15000 | | 50=2w+3w | | 7^(4y)=8 | | 6.9/(x−7.4)=3 | | (5x-1)2=125 | | 6.9÷(x−7.4)=3 | | $52.02-n=$38.45 | | 6.9/(x-7.4)=3 |